Megakaryocyte contribution to bone marrow fibrosis: many arrows in the quiver - Alessandro Malara; Vittorio Abbonante; Maria Zingariello; Anna Rita Franco Migliaccio; Alessandra Balduini (Mediterranean Journal of Hematology and Infectious Diseases)
In Primary Myelofibrosis (PMF), megakaryocyte dysplasia/hyperplasia determines the release of inflammatory cytokines that, in turn, stimulate stromal cells and induce bone marrow fibrosis. The pathogenic mechanism and the cells responsible for progression to bone marrow fibrosis in PMF are not completely understood. This review article aims to provide an overview of the crucial role of megakaryocytes in myelofibrosis by discussing the role and the altered secretion of megakaryocyte-derived soluble factors, enzymes and extracellular matrices that are known to induce bone marrow fibrosis. Additionally, we describe recent evidences showing that the role of megakaryocytes in tissue fibrosis is not limited to the bone marrow.